Korelasi Antara Kadar Lp-PLA2, MDA, F2-Isp di Serum dan Jaringan Aorta dengan Jumlah Sel Busa dalam Proses Aterogenesis pada Tikus Wistar - Retno Susilowati; Djanggan Sargowo; Rasjad Indra; Askandar Tjokroprawiro; Sri Widyarti (Jurnal Kardiologi Indonesia, 2012)
Background. Atherogenesiswas initiated by cholesterol deposits on foam cell in sub intimae of blood vessel stress oxidation. Atherogenesis in non- hypercolesterolemiausually undergoes an increased level of Lp-PLA2. It, therefore, needs to evaluate the role of Lp-PLA2in the foam cell formation. Aims. To explain the role of Lp-PLA2 in the foam cell forming, to correlate the level of Lp-PLA2 ,MDA, F2-Isp in aorta with foam cell number (FCs) as well as to correlate the level of Lp-PLA2 , MDA, F2-Isp contents in serumwith their contents in aorta and the correlation with FCs.Methods. 30 rats aged 2 months, with their weight averaging from 150-200g,were divided into the control group and the treatment one where the latterwas fed hyperlidemia for 2,8 and 12 weeks. The measurement level of LDL-C,MDA, F2-isp and Lp-PLA2in serum was performedas well as aorta and FCs. Data was analysed using anova, t-Test, path analysis and correlation. Results. Research result indicated that: (1) The level of MDA(a), F2-Isp(s) and Lp-PLA2(s) positively correlated with FCs, Lp-PLA(s)having the highestcorrelation value. (2) Lp-PLA2(a),MDA(s) and F2-Isp(s,a)did not correlate withFCs. (3) There was a positive correlation between Lp-PLA2 with MDA andF2-Isp in both serum and aorta.Conclusion. The enzyme of Lp-PLA2 acts as an activator in forming thefoam cell with stimulated stress oxidation.